PENGARUH STRUKTUR MODAL TERHADAP EARNING PER SHARE PADA PT TELEKOMUNIKASI INDONESIA TBK - Maimunah, Siti; Megasatya, Tiara Shinta (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2015)
Each company is always needed of funds or capital in order to get the needs of daily operations as well as to develop the company. In conducting the funding decision, the company is required to consider and analyze the sources and economically in order to finance the investment needs as well as business activities. The funding decisions will affect the companys capital structure. Investors and creditors use information as a measure funding the capital structure of the company. The purpose of this research was to test empirically the influence of capital structure to earnings per share. Based on the results of research and statistical tests that have been done, variable debt to asset ratio is partially no effect on earnings per share. Because of output t test showed that the results of the regression coefficient of variable debt to asset ratio is 2.042. This value is smaller than t table that is equal to 2.0796. And variable debt to equity ratio is partially an effect on earnings per share. Because based on output t test showed the results of the regression coefficient of variable debt to equity ratio produced is -3.998. This value is smaller than t table that is equal to -2.0796. Then Based on statistical test output F together (simultaneously) the independent variable (debt to asset ratio and debt to equity ratio) have an effect on earnings per share. This can be proven by the calculated F value generated at 22.302 larger than F table is 3,47 and it can be concluded that the capital structure (debt to asset ratio and debt to equity ratio) simultaneously or jointly effect on earnings per share.Â Key words: Debt to Asset Ratio, Debt to Equity Ratio, dan Earnings per Share